The estimated ex ante economic impact of Bt cowpea in Niger, Benin and Northern Nigeria - Gbègbèlègbè, S.D.; Lowenberg-Deboer, J.; Adeoti, R.; Lusk, J.; Coulibaly, O. (Wiley, 2015)
Genetically modified (GM) crops could increase economic growth and enhance living standards in Africa, but political issues have slowed the use of biotechnology. This is the first study that assesses the potential impact of GM crops in Africa while considering the preferences of producers and consumers towards GMOs as well as the income and price risks they face. The study uses a choice experiment to estimate the ex ante economic impact of a novel technology, Bacillus thuringiensis (Bt) cowpea, on producers and consumers in Benin, Niger and northern Nigeria. The experiment involves the simulation of a market transaction similar to those in open air markets in West Africa. During the market simulation, respondents are informed about the advantages and disadvantages, including health risks, of Bt cowpea. The results from the study suggest that cowpea growers and consumers in Benin and northern Nigeria prefer Bt to conventional cowpea for health safety reasons. The results estimate that social welfare in Benin, Niger and northern Nigeria would increase by at least US$11.82 per capita annually with Bt cowpea, if seed sectors are operating smoothly. With inefficiencies in seed sectors and the potential for cowpea acreage increase, the estimated social welfare increase in the region would be about US$1.26 per capita annually.